An optoelectronic resistive switching memory with integrated demodulating and arithmetic functions - Tan, Hongwei (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.